2020
DOI: 10.3389/fonc.2020.00181
|View full text |Cite
|
Sign up to set email alerts
|

miR-1323 Promotes Cell Migration in Lung Adenocarcinoma by Targeting Cbl-b and Is an Early Prognostic Biomarker

Abstract: Purpose: MicroRNAs are known to regulate cellular processes in non-small cell lung cancer (NSCLC) cells and predict prognosis. However, identification of specific microRNAs in NSCLC as potential therapeutic targets is controversial. We aim to determine the clinical significance of miR-1323 in the prognosis of patients with lung cancer and the potential mechanism. Patients and methods: A bioinformatics approach was used to screen the importance microRNA in NSCLC through the online GEO database (GSE42425). The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Considering the increased expression of miR-1323 in patients with GDM, ROC curves were plotted based on the miR-1323 expression and revealed that miR-1323 may be a potential diagnostic biomarker for patients with GDM. Abnormal serum miR-1323 expression has been reported to be a candidate biomarker for numerous other diseases, including lung adenocarcinoma ( 30 ) and breast cancer ( 31 ). Therefore, we hypothesized that serum miR-1323 may be a novel and effective diagnostic biomarker for patients with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the increased expression of miR-1323 in patients with GDM, ROC curves were plotted based on the miR-1323 expression and revealed that miR-1323 may be a potential diagnostic biomarker for patients with GDM. Abnormal serum miR-1323 expression has been reported to be a candidate biomarker for numerous other diseases, including lung adenocarcinoma ( 30 ) and breast cancer ( 31 ). Therefore, we hypothesized that serum miR-1323 may be a novel and effective diagnostic biomarker for patients with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) are a class of small non-coding RNAs (18-25 nucleotides in length) that act as post-transcriptional regulators of gene expression by direct binding to the 3' untranslated regions (3'UTRs) of target mRNAs; this binding induces mRNA degradation and/or translational repression (4). miRNAs participate in a number of biological processes, such as cell cycle progression, proliferation, invasion, migration and cell metabolism (5)(6)(7)(8). The regulatory role of miR-592 is context-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In addition, it has been demonstrated that miRNAs play crucial roles in the pathogenesis and progression of cancers through functioning as oncogenic or tumor suppressor. 17 For instance, upregulation of miR-1323, 18 miR-212-5p, 19 and miR-671-3p 20 was found in NSCLC tissues and cells and participated in the proliferation, migration, invasion, and apoptosis as oncogenes. In addition, the downregulation of miR-144, 21 and miR-140-3p 22 functioned as a tumor suppressor in the development of NSCLC.…”
Section: Introductionmentioning
confidence: 99%